Pay Inequality - Moene, Karl Ove; Wallerstein, Michael (Journal of Labor Economics, 1997)
We investigate the effects of wage compression through centralized collective bargaining when growth depends on the continual reallocation of labor from older, less productive plants to new, more productive plants. We first study the compression of wage differentials that derive from decentralized bargaining in heterogeneous plants. We then consider wage compression when wage difterentials arise from competition among employers over workers of differing quality. We show that wage compression through centralized bargaining can result in higher profits and greater entry of new plants than either decentralized bargaining or a competitive labor market.